Micro-manufacturing : design and manufacturing of micro-products - Koç, Muammer, 1968-; Özel, Tuğrul, 1967- (Hoboken, N.J. : Wiley, 2011)
"This book is the first of its kind to collectively address design-based and mechanical micro-manufacturing topics in one place. It focuses on design and materials selection, as well as the manufacturing of micro-products using mechanical-based micro-manufacturing process technologies. After addressing the fundamentals and non-metallic-based micro-manufacturing processes in the semiconductor industry, it goes on to address specific metallic-based micro-manufacturing processes, such as: micro-forming, micro-machining, micro-molding, micro-laser processing, micro-layered manufacturing, micro-joining, micro-assembly and materials handling, and microEDM and ECM. The book provides an in-depth understanding of materials behavior at micro-scales and under different micro-scale processing conditions, while also including a wide variety of emerging micro-scale manufacturing issues and examples"--
"This book is the first of its kind to collectively address design-based and mechanical micro-manufacturing topics in one place. It focuses on design and materials selection, as well as the manufacturing of micro-products using mechanical-based micro-manufacturing process technologies. After addressing the fundamentals and non-metallic-based micro-manufacturing processes in the semiconductor industry, it goes on to address specific metallic-based micro-manufacturing processes, such as: micro-forming, micro-machining, micro-molding, micro-laser processing, micro-layered manufacturing, micro-joining, micro-assembly and materials handling, and microEDM and ECM"--
Fundamentals of Micro-Manufacturing / Muammer Ko, Tugrul Ozel -- Micro-Fabrication Processes in Semiconductor Industry / Kasif Teker -- Modeling and Analysis at Micro-Scales / Takehiko Makino, Kuniaki Dohda -- Metrology, Inspection, and Process Control in Micro-Scales / Omkar G Karhade, Thomas R Kurfess -- Micro-Layered Manufacturing / Amit Bandyopadhyay, Vamsi K Balla, Sheldon A Bernard, Susmita Bose -- Micro-Laser Processing / Benxin Wu, Tugrul Ozel -- Polymer Micro-Molding/Forming Processes / Donggang Yao -- Mechanical Micro-Machining / Tugrul Ozel, Thanongsak Thepsonthi -- Micro-Forming / Muammer Ko, Sasawat Mahabunphachai -- Micro-Electro Discharge Machining (EDM) / Muhammad Pervej Jahan, Abu Bakar Md Ali Asad, Mustafizur Rahman, Yoke San Wong, Takeshi Masaki -- Metal Injection Molding at Micro-Scales (MIM) / Gang Fu, Ngiap Hiang Loh, Shu Beng Tor, Bee Yen Tay -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Microfabrication; Micromachining; Manufacturing processes; Manufacturing processes; Microfabrication; Micromachining; TECHNOLOGY & ENGINEERING -- Material Science; TECHNOLOGY & ENGINEERING -- Industrial Technology; TECHNOLOGY & ENGINEERING -- Technical & Manufacturing Industries & Trades; TECHNOLOGY & ENGINEERING -- Industrial Engineering; TECHNOLOGY & ENGINEERING -- Manufacturing; Manufacturing processes; Microfabrication; Micromachining; Electronic books; Electronic books